PENGARUH ETIKA AUDITOR, KOMPETENSI AUDITOR, FEE AUDIT DAN MOTIVASI AUDITOR TERHADAP KUALITAS AUDIT - Jehaba, Lidvina Apriani; Sulistyo, Sulistyo; Wirshandono, Doni (Jurnal Riset Mahasiswa Akuntansi, 2017)
Audit quality is the probability that an auditor will find and report violations in his client'saccounting system, systematic and independent checks to determine activities, quality and resultsin accordance with planned arrangements and whether the arrangements are implementedeffectively and match the objectives. The purpose of this study is to determine the effect of auditorethics, auditor competence, audit fees and auditor motivation on audit quality. The population inthis study is the Auditor who works in Malang City Public Accountant Office. The results of thisstudy indicate that auditors ethically influence audit quality, auditor competence influences auditquality, audit fees affect audit quality, auditor motivation influences audit quality.